ADOLESCENT PARTICIPATION IN YOUTH INFORMATION AND COUNSELLING CENTRE IMPROVES BETTER KNOWLEDGE ON HIV AIDS AND EARLY MARRIAGE PREVENTION - Anggraeni, Ike; Nurrachmawati, Annisa; Triani Putri, Irda (Jurnal Biometrika dan Kependudukan, 2025)
Youth Information and Counseling Centers (YICC) im to enhance adolescents’ reproductive health knowledge through peer-based education. Despite their significance, the effectiveness of such programs remains inadequately evaluated, especially in Indonesia, where adolescent reproductive health challenges, such as early marriage and HIV/AIDS, persist. This study explores the relationship between YICC participation and adolescents’ knowledge of HIV/AIDS and early marriage prevention in East Kalimantan. A cross-sectional survey was conducted among 830 adolescents aged 10-24 using a validated online questionnaire. Descriptive statistics, Kruskal-Wallis tests, ANCOVA, and logistic regression were employed to analyze knowledge differences and predictors, controlling for sociodemographic factors. Results revealed that 71.8% of adolescents were aware of YICC, yet only 38.2% participated in its activities, and 21.4% were formal members. YICC participants showed significantly greater knowledge of HIV/AIDS and the ideal marriage age (p < 0.01), though no significant differences were found in attitudinal scores. ANCOVA indicated that YICC participation was an important predictor of knowledge, even after adjusting for parental education, internet access, and residence. Logistic regression further showed that YICC participants were 1.9 times more likely to possess high knowledge compared to non-participants (AOR = 1.90; 95% CI: 1.30-2.70; p = 0.001). Key predictors of higher knowledge included parental education, internet access, and urban residence. These findings highlight the importance of increasing YICC participation and integrating digital and school-based strategies to enhance adolescent reproductive health education.